2016
DOI: 10.1002/jnr.23838
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, electrophysiological, and biochemical markers of peripheral and central nervous system disease in canine globoid cell leukodystrophy (Krabbe's disease)

Abstract: Globoid cell leukodystrophy (GLD), or Krabbe disease, is a debilitating and always fatal pediatric neurodegenerative disease caused by a mutation in the gene encoding the hydrolytic enzyme galactosylceramidase (GALC). In the absence of GALC, progressive loss of myelin and accumulation of a neurotoxic substrate lead to incapacitating loss of motor and cognitive function and death typically by two years of age. To date there is no cure. Recent convincing evidence of the therapeutic potential of combining gene an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 22 publications
1
41
0
Order By: Relevance
“…Histological studies in Krabbe disease have demonstrated enlarged peripheral nerves with signs of de‐ and dysmyelination and fibrotic changes . Perineural edema has been demonstrated in a mouse model and infiltration of multinucleated macrophages (“globoid cells”) is a known characteristic of Krabbe disease …”
Section: Discussionmentioning
confidence: 99%
“…Histological studies in Krabbe disease have demonstrated enlarged peripheral nerves with signs of de‐ and dysmyelination and fibrotic changes . Perineural edema has been demonstrated in a mouse model and infiltration of multinucleated macrophages (“globoid cells”) is a known characteristic of Krabbe disease …”
Section: Discussionmentioning
confidence: 99%
“…Histopathology of the brain shows diffuse, massive accumulations of previously described globoid cells, as well as extensive gliosis and perivascular lymphocytic cuffing confined to the white matter with sparing of gray matter (153). Demyelination of all areas of the brain, auditory system, and peripheral nerves is present in canine patients (149). Psychosine is elevated in tissues and CSF of GLD dogs (154) increasing significantly over time and may be a potential biomarker of disease (149).…”
Section: Globoid Cell Leukodystrophy In Caninesmentioning
confidence: 99%
“…In addition to humans, globoid cell leukodystrophy (GLD) has been documented in several other species, including dogs, mice, monkeys, and sheep. In dogs, GLD has been reported in Cairn terriers, West Highland Terriers, Australian Kelpies, Beagles, Poodles, and mixed breeds (144)(145)(146)(147)(148)(149)(150). As with NCL, GLD is thought to be the same disease occurring in different species, maximizing the usefulness of canine models in developing therapies for humans with GLD.…”
Section: Globoid Cell Leukodystrophy In Caninesmentioning
confidence: 99%
See 2 more Smart Citations